Financial incentives and study duration in higher education - Trude Gunnes; Lars J. Kirkebøen; Marte Rønning (Statistics Norway, Research Department, 2012)
This paper investigates to which extent students in higher education respond to financial incentives by adjusting their study behavior. Students in Norway who completed certain graduate study programs between autumn 1990 and 1995 on stipulated time were entitled to a restitution of approximately 3,000 USD from the Norwegian State Educational Loan Fund. Comparing treated and untreated (control) programs in a difference-in-difference framework, we find that the average delay in the treatment group decreased by on average 0.8 semester during the reform period, and by 1.5 semesters in the following two years. Number of years treated matter strongly, with delays reduced by 0.23 semesters per year treated. Furthermore, there is some indication that it is important that treatment starts before the final part of the educational programs. The share of on-time graduation increases by 3.8 percentage points per year treated, from a pre-reform level of about 20 percent. Thus, a large share of the restitutions given will be for students who would otherwise not have graduated on time. A series of robustness checks indicate that our estimated effects do not reflect differential trends or omitted variables.
Keywords: D01; H52; I22; I28; 330; Financial incentives; higher education; on-time graduation; semesters delayed; difference-in-difference